2008
DOI: 10.1104/pp.107.113282
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Induced Turnover of the Arabidopsis IRON-REGULATED TRANSPORTER1 Metal Transporter Requires Lysine Residues    

Abstract: Iron is an essential micronutrient but is toxic if accumulated at high levels. Thus, iron uptake and distribution in plants are controlled by precise regulatory mechanisms. IRON-REGULATED TRANSPORTER1 (IRT1) is the major high affinity iron transporter responsible for iron uptake from the soil in Arabidopsis (Arabidopsis thaliana). Previously, we showed that IRT1 is subject to posttranscriptional regulation; when expressed from the constitutive cauliflower mosaic virus 35S promoter, IRT1 protein accumulates onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
89
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 60 publications
5
89
1
2
Order By: Relevance
“…Lys-146 or Lys-171 were found to be required for the degradation of IRT1. Plants expressing IRT1 with substitutions at these two residues accumulated more Fe than the wild type (Kerkeb et al, 2008). This report was the first to support the involvement of ubiquitination in the degradation of IRT1.…”
Section: Introductionsupporting
confidence: 48%
See 3 more Smart Citations
“…Lys-146 or Lys-171 were found to be required for the degradation of IRT1. Plants expressing IRT1 with substitutions at these two residues accumulated more Fe than the wild type (Kerkeb et al, 2008). This report was the first to support the involvement of ubiquitination in the degradation of IRT1.…”
Section: Introductionsupporting
confidence: 48%
“…IRT1 is a broad substrate range metal ion transporter that can transport Fe 2+ , Zn 2+ , Mn 2+ , Co 2+ , and Cd 2+ either expressed in yeast or in plants (Korshunova et al, 1999). Previous studies have suggested that in Arabidopsis, Fe-induced turnover of IRT1 is regulated by ubiquitination (Kerkeb et al, 2008;Barberon et al, 2011). The second intracellular loop of IRT1 is thought to be an E3 interacting and ubiquitination domain (Kerkeb et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A posttranslational control of IRT1 protein by ubiquitination was identified (15,16). IRT1 protein was shown to localize to early endosomes/trans-Golgi network compartments (EE/TGN) as a result of monoubiquitin-and clathrin-dependent endocytosis and is targeted to the vacuole for degradation via late endosomes (LE) (15).…”
mentioning
confidence: 99%